THE USE OF PRAGMATICS DEIXIS IN THE E-PAPER “ADVANTAGE #4: MEANINGFUL ENGAGEMENT” - Renggi Vrika; Meli Fauziah; Adam Mudinillah (Institut Pendidikan Tapanuli Selatan, 2022)
Deictic expression usually found both in written and spoken context. Deictic or deixis means pointing or indicating which comes from a Greek word. In this research, the researcher analyzed the deictic expression that had been included in the “Advantage #4: Meaningful engagement” text in The Jakarta Post E-PAPER. This research was qualitative research which content analysis that applied to the written or visual material. The researcher wanted to find the deictic expression in the text and gave an interpretation of the expression. There were some kinds of the deictic expression in the “Advantage #4: Meaningful engagement” text in The Jakarta Post E-PAPER. The person deixis that was involved were “us, Indonesia students, it, the students, your malnourished children, you, themselves, them”. The time deixis was “in 1998, last year, evening”. The place deixis that was involved in this text were “there, high school, the school, university, Trisakti University, Hotel Indonesia traffic circle, and the Presidential Palace”. Discourse deixis that was involved in this text was “there, it, and that”. And also the social deixis that was involved was “the president”. So, those are the deictic expression that included in the text in The Jakarta Post E-PAPER.